Stable and robust design of active disturbance-rejection current controller for permanent magnet machines in transportation systems - Diab, Ahmed M.; Bozhko, Serhiy; Galea, Michael; Gerada, Christopher (2020)
Active disturbance-rejection control (ADRC) as a current control (CC) method for ac drive systems has been recently shown to have significant strengths. Its robustness to system uncertainties and its high disturbance-rejection capability render it an attractive control scheme for various mobile applications. Until now, however, all the known tuning methods available in literature are based on a number of assumptions that may lead to the degraded drive performance and even to the loss of stability. This article, thus, provides a rigorous analysis and proposes a new CC design method based on the ADRC technique. The design derives a generic closed-loop transfer function considering system delays and the dynamics of the extended state observer. Based on this analysis, a tuning method able to guarantee a set performance to avoid unstable operation is thus proposed. The effects of model uncertainties on the current loop system stability and robustness are also analyzed and reported. A tuning criterion to enhance system robustness and to improve its dynamic performance is developed and validated experimentally on a case study system.